Prototipe Sistem Deteksi Kemacetan Jalan Raya Berbasis Internet Of Things (IoT) - Phisca Aditya Rosyady; Muslih Rayullan Feter; Zakky Ahmad Ikhsan M (Institut Teknologi Dirgantara Adisutjipto, 2022)
Along with the progress of the times and technology is currently increasing the number of motorized vehicles on the highway. However, this increase in the number of motorized vehicles is not matched by an increase in road volume capacity, causing traffic congestion. The purpose of this study was to find out information about traffic conditions at highway intersections. This research is a prototype that describes a four-way intersection that has infrared sensors in each path. This infrared sensor is used as a vehicle detector. Tests on the prototype made various traffic conditions that are relevant to the actual situation. This research utilizes the concept of the Internet of things (IoT) prototype which is made to be connected to the internet network so that users can find out traffic conditions remotely and in real time. One of the information media used in this research is Twitter. The results of this study indicate that the prototype made can work well. The infrared sensor used can work optimally and can detect vehicles precisely at a sensitivity range of 4.5 cm. The average delay in sending notification tweets is 18 seconds.